William Wredes kaiserzeitliche Messiasgeheimnistheorie = William Wrede’s imperial-era theory of the Messianic secret - Klumbies, Paul-Gerhard (Das Markusevangelium als Erzählung, 2018)
William Wrede’s theory of the messianic secret in the gospels is probably the most influential hypothesis in modern research on Mark’s gospel. Since its publication in 1901, it has become an integral part of the investigations of the Markan Christology, albeit with modifications. Behind Wrede’s theory are undiscussed dogmatic presuppositions from past Christological debates as well as contemporary-historical influences that extend to the use of the Messiah title. It is distinctive that the imperial-era rulers’ presentation of the late nineteenth century has an impact on Wrede’s depiction. With it he literally sets Jesus, according to the zeitgeist of his era, an individual monument (Individualdenkmal).